Práticas educativas no ensino de ciências: experiências de docentes do campo/cidade - Melo, Joedna Nobre de (Universidade Federal Rural do Semi-Árido, 2020)
This course conclusion work refers to the research on the educational practices chosen by the teachers in the area of Nature Sciences, intended for students from the field in a public high school institution, located in the municipality of Portalegre/RN. The objective of this study was to investigate the educational practices of the teaching staff in the respective area in order to identify the planning of the classes and its specificities in working with students from the field, understand their contextualization forms of the contents explained with this public and to analyze the methodological practice of teachers in the respective classes in which they work. This research had the participation of three professors responsible for the disciplines of Chemistry, Biology and Physics. The accomplishment of this work was the result of a qualitative research carried out in two moments: At first through an interview script and, in the second moment, through observations in the classroom. For data collection, the content analysis of author Laurence Bardin (1977) was used. In view of the results of this work the use of the textbook as the main teaching tool was identified and there were also attempts to contextualize the contents through dialogues established in the classroom. With this, it was clear that the area of Nature Sciences also requires adaptation of teaching according to the realities of life of the students attended.
Keywords: Práticas educativas; Ciências da natureza; Educação do campo; Educational practies; Nature sciences; Country education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL